ANALISIS KALIMAT PERSUASIF PADA IKLAN PRODUK G2G OLEH INFLUENCER MAHARAJASP DI MEDIA SOSIAL TIKTOK - Selvi Aulia Futri; Nisa Arianti Sri Lestari; Robi Abdul Rohim; Irfa Rufaidah; Iis Lisnawati (Jurnal Bastra (Bahasa dan Sastra), 2025)
This article discusses the development of TikTok as a major platform in digital marketing strategies, especially in Indonesia. TikTok is not only used for creativity, but also as an effective business medium in reaching young audiences through persuasive and creative content. Features such as the "For You Page" (FYP) help content go viral, opening up great opportunities for business people and creators. Influencers, including celebrities, play an important role in shaping consumer perceptions and purchasing decisions. This article aims to influence readers' emotions to be interested in buying products, by emphasizing the importance of persuasive communication. Specifically, this article analyzes the use of persuasive sentences in G2G product promotions by MaharajaSP influencers on TikTok, using a descriptive qualitative approach. The results of the analysis show that MaharajaSP is effective in using persuasive sentences to attract attention, create urgency, and provide recommendations, thereby increasing the effectiveness of product marketing on TikTok.